1.2 V differential difference current conveyor using MIGD MOST technique and its applications - Kumngern, Montree; Khateb, Fabian; Phatsornsiri, Punnavich; Jongchanachavawat, Wirote; Kulej, Tomasz; Torteanchai, Usa; Rattanasuttikan, Manurak (My University, 2023)
This paper presents a new differential difference current conveyor (DDCC), realized using multiple-input gate-driven MOS transistor (MIGD MOST) technique. The application of MIGD MOST can reduce the number of differential pairs in the input stage of the DDCC, thus simplifying its overall structure. Unlike previous DDCC, the output stage of the circuit operates in super class-AB, that offers low static power consumption, high load driving capability and improved gain-bandwidth product (GBW).The proposed DDCC can work with the supply voltage of 1.2 V and consumes 44.2 μW of power. The proposed DDCC has been used to realize a versatile circuit that can work as a universal filter or a quadrature oscillator into a single topology. When the circuit works as a universal filter, it can realize low-pass, band-pass, high-pass, band-stop and all-pass voltage responses. The natural frequency and the quality factor of these responses can be orthogonally controlled. When the circuit works as a quadrature oscillator, the condition and the frequency of oscillators can be orthogonally controlled. The proposed MIGD DDCC and the proposed universal filter and quadrature oscillator have been simulated with SPICE, using 0.18 μm CMOS process parameters to prove the functionality and workability of the new circuits.
Keywords: Differential difference current conveyor; Low-voltage low-power; Multiple-input gate-driven MOS transistor; Quadrature oscillator; Universal filter